Existence of cholera outbreak, challenges, and way forward on public health interventions to control cholera outbreak in Guraghe Zones, southern Ethiopia, 2023 - Berhe, Tamirat Melis; Fikadu, Yohannes; Sahle, Tadesse; Hailegebireal, Aklilu Habte; Eanga, Shamil; Ketema, Temesgen; Wolde, Shimelis Getu (Frontiers in Public Health, 2024)
In Ethiopia, despite major improvements seen in health service delivery system, the country continues to be significantly affected by cholera outbreaks .Cholera remains a significant public health problem among the vulnerable populations living in many resourcelimited settings with poor access to safe and clean water and hygiene practices. Recurring cholera outbreaks are an indication of deprived water and sanitation conditions as well as weak health systems, contributing to the transmission and spread of the cholera infection.Objective: To assess the cholera outbreak, its challenges, and the way forward on public health interventions to solve the knowledge and health service delivery gaps related to cholera control in Guraghe Zone, Ethiopia, 2023.Methods: Active surveillance of the cholera outbreak was conducted in all kebeles and town administrative of Guraghe zone from 7/8/2023-30/10/2023. A total of 224 cholera cases were detected during the active surveillance method. Data obtained from Guraghe zone offices were exported to SPSS version 25 for additional analysis. The case fatality rate, incidence of the cases, and other descriptive variables were presented and described using figures and tables.Result: A total of 224 cholera cases were detected through an active surveillance system. In this study, the case fatality rate of cholera outbreak was 2.6 %. To tackle the cholera outbreak, the Guraghe zone health office collaborated with other stakeholders to prepare four cholera treatment centers. The absence of OCV, inaccessible safe water, low latrine coverage, inappropriate utilization of latrines, and absence of cholera laboratory rapid diagnostics test in Guraghe Zone are barriers to tackling the outbreak.Ethiopia National Cholera Plan targeted eradicating cholera by 2030,222 cholera outbreak occurred in Guraghe Zone, Ethiopia. To minimize and control cholera mortality rate oral cholera vaccinations should be employed in all areas of the region. Sustainable WASH measures should be guaranteed for the use of safe water and good hygiene practices. Early diagnosis and treatment should be initiated appropriately for those who are infected.